Border detection in digital images: An approach by fuzzy numbers - Boaventura, Ines Ap Gasparotto [UNESP]; Gonzaga, Adilson (My University, 2007)
The purpose of this paper is to introduce a new approach for edge detection in gray shaded images. The proposed approach is based on the fuzzy number theory. The idea is to deal with the uncertainties concerning the gray shades making up the image, and thus calculate the appropriateness of the pixels in relation to an homogeneous region around them. The pixels not belonging to the region are then classified as border pixels. The results have shown that the technique is simple, computationally efficient and with good results when compared with both the traditional border detectors and the fuzzy edge detectors. © 2007 IEEE.
Keywords: Algebra; Detectors; Edge detection; Fuzzy logic; Fuzzy rules; Fuzzy sets; Image enhancement; Intelligent control; Number theory; Pixels; Systems analysis; Border detection; Computationally efficient; Digital imaging; Edge detectors; Fuzzy numbers; International conferences; New approaches; Systems design; Intelligent systems